Acute Effects of New Zealand Blackcurrant Extract on Cycling Time-Trial Are Performance Dependent in Endurance-Trained Cyclists: A Home-Based Study - Stefano Montanari; Sam D. Blacker; Mark E. T. Willems (Sports, 2023)
The intake of anthocyanin-rich New Zealand blackcurrant (NZBC) extract (300 mg per day) over a week enhanced 16.1 km cycling time trial (TT) performance in endurance-trained cyclists without acute performance effects. In the present study, the acute effects of an intake of 900 mg of NZBC extract 2 h before performing the 16.1 km cycling TT were examined. A total of 34 cyclists (26 males; 8 females) (age: 38 ± 7 years, <semantics><mover accent="true">V˙</mover></semantics>O2max: 57 ± 5 mL·kg−1·min−1) completed 4 16.1 km TTs (2 familiarization and 2 experimental trials) over 4 mornings on a home turbo-trainer connected with the online training simulator ZWIFT. There was no difference in time to complete the 16.1 km TT between conditions (placebo: 1422 ± 104 s; NZBC extract: 1414 ± 93 s, p = 0.07). However, when participants were split between faster (<1400 s; 1 female; 16 males) and slower (>1400 s; 7 females; 10 males) cyclists based on average familiarization TTs, a difference in TT performance was observed only in the slower group (placebo: 1499 ± 91 s; NZBC extract: 1479 ± 83 s, p = 0.02). At 12 km (quartile analysis), power output (p = 0.04) and speed (p = 0.04) were higher compared to the placebo with no effects on heart rate and cadence. The acute effects of 900 mg of NZBC extract on a 16.1 km cycling time-trial may depend on the performance ability of male endurance-trained cyclists. More work is needed to address whether there is a sex-specific time-trial effect of NZBC extract independent of performance ability.